Isolation, Identification and Pathogenicity of Seed borne fungi of some barley cultivars - Ramadan, Nadeem A.; Zrary, Taha J. O. (Sulaimani Journal for Pure and Applied Sciences, 2014)
One hundred seeds were tested for each cultivars according to ISTA technique and using agar plate method. The pathogenicity test was conducted to study the effect of 6 fungal pathogen on pre and post emergence damping off and survival damping off seedling by inoculation of soil .Seven fungal genera Alternaria,Aureobasidium, Cladosporium, Drechslera, Penicillium , Rhizoctonia and Stemphylium were isolated from Barley seeds from Hawler governorate at season 2006. The Alternaria isolated at highest occurrence percentage (%75.2),while the Stemphylium isolated record the lowest incidence percentage (%0.1).Six fungal genera Alternaria, Aureobasidium, Cladosporium , Drechslera, Rhizoctonia and Stemphylium were isolated from Barley seeds at the season of 2007. The results obtained that the control significantly increases pre- emergence damping off seedlings after 10 days of sowing of seeds, the mean value was (1.08) as compared with fungal pathogen treatment which decreases their plant mean values obtained for Alternaria,Aureobasidium, Curvularia, Drecslera, Stemphylium and Rhizoctonia were recoded respectively .The ICARDA cultivar significantly affected which increased the post damping off seedlings their value was (3.0476) as compare with other cultivars. The results indicate that survival significantly increased their values were 7.833 as compared with control 8.916.
Keywords: Barley; Seed health testing; Fungi